Use of direct oral anticoagulants in ICU patients. Part II – Clinical evidence - Wahab, Abdul; Patnaik, Rupali; Gurjar, Mohan (Anestezjologia Intensywna Terapia, 2021)
During the last decade, utilization of direct oral anticoagulants (DOACs) has increased due to their pharmacokinetic profile and the fact that they are non-inferior to warfarin in the prevention of stroke in patients with atrial fibrillation, as well as for the treatment of venous thromboembolism. However, there are few studies about their use in critically ill patients. This article aims to review available evidence on the use of DOACs in the indicated conditions and anticoagulant management of medical or surgical patients receiving DOAC before intensive care unit (ICU) admission. The rapidly changing pathophysiology and heterogeneous nature of critically ill patients combined with limited evidence often leads to a high degree of individualization of DOAC regimens in ICU patients. This article is the second part of the narrative review series on the use of DOACs in ICU patients, focusing on current “Clinical evidence”. “Applied pharmacology” has been described in the first part.